(untitled) (Global Journals of Research in Engineering, 2017)
Sports biomechanics is an analysis of sports’ activities and professional athletes in general. It can plainly be called the Physics of Sports. In this sub division of biomechanics, the principles of mechanics are incorporated to gain a better insight of athletic performance via computer simulation, mathematical modelling and measurement. This paper briefly describes about the various methods in which biomechanics has enabled the athletes to perform better while being safe.